Susuks (charm needles) in the craniofacial region - Nambiar, P.; Ibrahim, N.; Tandjung, Y.R.M.; Shanmuhasuntharam, P. (2008)
Objectives. We conducted a study to determine the numbers of susuks (charm needles) and their distribution in the craniofacial region of susuk wearers, and the sex, racial affiliation, and age of the wearers. In addition, we sought to determine whether the presence of susuks posed any potential hazard to patients undergoing magnetic resonance imaging (MRI). Methods. We studied various radiographs of 33 susuk wearers (age range, 33-69 years) and investigated the most common sites of insertion in the craniofacial region. A susuk was also suspended inside a 1.5-T MRI machine to determined whether it was attracted by the machine's magnet. Results. The largest number of susuks that we observed in the craniofacial region was 39 pins, and susuks were particularly numerous in Malay Muslim women. Other sites with susuks were the maxillofacial region (except the temporomandibular region) and the forehead. The susuks showed no ferromagnetic characteristics. Conclusions. As susuks are made from gold, they are generally biocompatible with human tissue and do not cause problems to their wearers. Gold and the other minor metal constituents found in susuks have no ferromagnetic characteristics and therefore pose no hazard to patients undergoing MRI.